Toxicity Test on Taro Leaf Extract (Colocasia Esculenta L. Schoot) as Mouthwash to BHK-21 Fibroblast Cell Culture in Denture Users - Meilena, Tiara; Fabiansyah, Januar Cidie; Djulaeha, Eha; Hidayati, Hanoem Eka (Faculty of Dental Medicine Universitas Airlangga, 2018)
Background: One of requirements for a material to be used in dentistry is that the material must be non toxic and non irritant, as well as have biocompatibility properties, not triggering a detrimental effect on the biological environment, both locally and systemically. The first-line tests that must be conducted is in vitro tests, one of which is MTT Assay. Samples used in this research were fibroblast cells (cultured BHK-21 cells) since fibroblasts are the most important and largest components in pulp, periodontal ligament, and gingiva. Purpose: This research aimed to determine toxicity effect of taro leaf extracts (Colocasia esculenta L. Schoot) on BHK-21 fibroblast cells. Methods: This research is an experimental laboratory research using Post Test Only Control Group design. The research treatment are the administration of Taro leaf extract (Colocasia esculenta L. Schoot) with 100%, 80%, 60%, and 40% concentration on BHK-21 fibroblast cell. Results: The fibroblast cell life percentage in 100%, 80%, 60%, and 40% concentration respectively are 106,3%, 50,9%, 36,2%, and 30,1%. The toxicity results are obtained using MTT assay technique after 24 hours. The optical density absorbency values are read by ELISA reader and represent life cell viability. Conclusion: Taro leaf extract (Colocasia esculenta L. Schoot) at a concentration above 80% is considered as non-toxic material to BHK-21 fibroblast cells